RESPON MASYARAKAT TERHADAP PEMANFAATAN HHBK KEMIRI (Aleurites Moluccana Wild) DI DESA MIRE KECAMATAN ULUBONGKA KABUPATEN TOJO UNA-UNA - Firawati, Firawati; Rachman, Imran; Hamzari, Hamzari (Universitas Tadulako, 2020)
Forest is an area that is overgrown with thick trees and other plants. We can find forests in both the tropics and cold climates, in the lowlands and in the mountains, on small islands and on large continents, forests are a collection of plants and plants, especially trees or other woody plants, and these cannot be separated by HHBK, this made research interesting about the community's response to the utilization of the Candlenut Non-Timber Forest Products (Aleurites moluccana Willd). The purpose of this study was to determine how the community's response to the utilization of HHBK candlenut in Mire Village, Ulubongka District, Tojo Una-Una Regency, Central Sulawesi.This research was conducted in 2 months, from November to December 2019, and respondents were determined by purposive sampling. With data analysis using descriptive analysis methods, so that results are more detailed, From the characteristics of the respondents obtained through data analysis with descriptive material 1 (disagree) 3 (less agree) 5 (agree) The results showed that the response of the people of Mire Village to the use of hazelnut NTFP to bring prosperity to the community they responded was in the high level category or agreed, while the analysis of the data with scaling showed the community response to the utilization of hazelnut IPH by a percentage (200) High, why is it high because the level of community understanding of the hazelnut NTFPs is very good and this is also the result of Likert scale calculations.Keywords: Forest, Candlenut, Analysis.